Heat-treatment-free high-strength and high-toughness die-casting aluminum alloy material as well as preparation method and application thereof

By developing a high-strength and high-tough die-cast aluminum alloy material without adding rare earth elements and free of heat treatment, the high proportion of recycled aluminum and specific elements is used to solve the problem of heat treatment in the automotive industry that existing aluminum alloy materials require heat treatment, and achieve the realization of High strength, high toughness and low cost material properties.

CN119392055AInactive Publication Date: 2025-02-07YADELIN MACHINERY SUZHOU CO LTD

Patent Information

Application Number
CN202411633811.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing aluminum alloy materials require heat treatment in the application of the automotive industry, which increases production costs and has problems such as bubbles and deformation, and the mechanical properties are not enough to meet the needs of complex structural parts.

Method used

Develop a high-strength, high-tough die-cast aluminum alloy material without adding rare earth elements and heat-free treatment, which improves the material by optimizing composition and process, including the use of a high proportion of recycled aluminum to specific elements (5

Benefits of technology

It is achieved that the tensile strength, yield strength and elongation after break of the material can reach high standards under high pressure die-casting conditions of ≥4400T, meeting the needs of complex automotive structural parts and reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392055A_ABST
    Figure CN119392055A_ABST
Patent Text Reader

Abstract

The invention discloses a heat-treatment-free high-strength high-toughness die-casting aluminum alloy material which comprises the following components in percentage by mass: 7-8% of silicon, less than or equal to 0.14% of iron, less than or equal to 0.008% of copper, 0.6-0.7% of manganese, 0.2-0.26% of magnesium, less than or equal to 0.005% of zinc, less than or equal to 0.001% of calcium, less than or equal to 0.003% of lead, less than or equal to 0.0003% of antimony, less than or equal to 0.00008% of beryllium, 0.08-0.15% of titanium and 0.016-0.026% of strontium. The sum of the impurities is smaller than or equal to 0.15%, the content of a single impurity element is smaller than or equal to 0.05%, and the proportion of the mass percentage content of manganese to the mass percentage content of iron is larger than 5 and smaller than 7. According to the heat-treatment-free high-strength and high-toughness die-casting aluminum alloy material, through formula design and control over Mn / Fe being larger than 5 and smaller than 7, a needle-sheet-shaped Fe-rich phase is reduced, the purpose of improving the mechanical property of the aluminum alloy material is achieved, and the porosity and the mechanical property of the aluminum alloy material are good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of alloy materials, and specifically relates to a high-strength and high-toughness die-casting aluminum alloy material that does not require the addition of rare earth elements and does not require heat treatment, a preparation method of the aluminum alloy material, and application of the aluminum alloy material in large, thin-walled complex automotive structural parts, such as shock towers and battery pack crossbeams. When used in (≥4400T) high-pressure die-casting, the aluminum alloy material can ensure good tensile strength, yield strength and elongation after fracture. Background Art

[0002] The global automotive industry is committed to lightweighting vehicles. Among them, the idea of ​​replacing conventional automotive steel with aluminum alloys has been widely recognized and applied. At present, Germany's Rheinmetall's Silafont-36 series aluminum alloys and Alcan's Aural-2 and Aural-3 alloys have been widely used in the automotive industry. However, the above alloys require heat treatment to meet the needs of the automotive industry, which not only increases the production process and causes an increase in costs, but also reduces the product qualification rate due to problems such as bubbles and deformation caused by heat treatment.

[0003] In order to solve the above-mentioned bottleneck of aluminum alloy application, Alcoa's EZCAST series C611 heat-treatment-free Al-Si die-cast aluminum alloy has been successfully applied to the all-aluminum body of Audi A8. At present, the heat-treatment-free materials used in China are in the early stages. The cast products are prone to cold shut and undercasting, and the internal shrinkage pores are difficult to meet the use requirements of the automotive industry. In addition, the mechanical properties are low. These problems limit the application prospects of die-cast aluminum alloy materials. Therefore, it is necessary to develop a high-strength and high-toughness die-cast aluminum alloy material that meets the performance requirements of automotive structural parts and does not require heat treatment.

[0004] Patents in the prior art, such as application number 202311240910.2, named A high-yield, heat-treatment-free aluminum alloy material for thin-wall welding process of new energy vehicles and its preparation method, wherein the disclosed material is used in hydraulic die forging, targeting the high yield required under the welding process, rather than high-pressure casting and high-strength and toughness materials.

[0005] Another example is the patent application number 202311414034.0, named "A renewable high-strength and toughness heat-treatment-free aluminum alloy and its preparation method and die-casting process". The aluminum liquid process in this patent is roughly as follows: material selection and feeding → refining and slag removal → component fine-tuning, metamorphism and refinement → refining and degassing → second slag removal → online degassing → filtration → casting and molding; the raw aluminum is 100% aluminum ingots for remelting, which avoids the introduction of too many impurities; at the same time, the "filtration" step can make the aluminum liquid purer, but the material selection and "filtration" process will result in an increase in cost.

[0006] Another example is the patent application number 202310223358.X, which is titled "A heat-treatment-free high-strength and toughness die-cast aluminum alloy and its preparation method and products". In this patent, "the aluminum raw material is pure aluminum or one or more of aluminum ingots for remelting with a quality not lower than A199.80", and at the same time, "the said S2 is added with the said first-level recycled materials not exceeding 30% of the total aluminum demand weight", that is, in order to ensure the performance, the aluminum raw materials in this patent use high-purity primary aluminum with a high-quality ratio and first-level recycled materials with low pollution. At the same time, in industrial production, the work of sorting recycled materials will be added, which is expensive in production costs and is not suitable for industrial production.

[0007] The disclosure of the above background technology content is only used to assist in understanding the inventive concept and technical solution of the present invention. It does not necessarily belong to the prior art of this patent application. In the absence of clear evidence that the above content has been disclosed before the filing date of this patent application, the above background technology should not be used to evaluate the novelty and creativity of the present application. Summary of the invention

[0008] In view of this, in order to overcome the defects of the prior art, the purpose of the present invention is to provide a high-strength and high-toughness die-casting aluminum alloy material that does not require heat treatment. Without adding rare earth elements, when used for high-pressure die-casting ≥4400T, it can ensure good tensile strength, yield strength and elongation after fracture.

[0009] In order to achieve the above object, the present invention adopts the following technical solutions: A high-strength and high-toughness die-cast aluminum alloy material that does not require heat treatment, the aluminum alloy material includes silicon: 7-8%, iron: ≤0.14%, copper: ≤0.008%, manganese: 0.6-0.7%, magnesium: 0.2-0.26%, zinc: ≤0.005%, calcium: ≤0.001%, lead: ≤0.003%, antimony: ≤0.0003%, beryllium: ≤0.00008%, titanium: 0.08-0.15%, strontium: 0.016-0.026%; the remainder is impurities and aluminum, wherein the total impurities are ≤0.15%, a single impurity element is ≤0.05%, and the mass percentage content of manganese to the mass percentage content of iron is greater than 5 and less than 7 (5<Mn / Fe<7). Within a specific range, the use of Mn element to modify the cast aluminum alloy rich in Fe element can effectively transform the needle-shaped Fe-rich phase into the Chinese character-shaped Fe-rich phase, thereby achieving the effect of improving the strength of the alloy. However, excessive Mn content in the alloy will promote the formation of pores, so the ratio is controlled within 7.

[0010] According to some preferred embodiments of the present invention, the raw materials of the aluminum alloy material include primary aluminum and recycled aluminum, electrolytic manganese, manganese additives (containing 75% manganese), pure magnesium ingots, aluminum-titanium alloy with a titanium content of 10%, 3303 specification metallic silicon, and Al-Sr alloy with a Sr content of 10%.

[0011] According to some preferred embodiments of the present invention, the primary aluminum is an A00 aluminum ingot having an aluminum content greater than 99.75%, and the recycled aluminum is scrap aluminum having the same alloy grade as the primary aluminum.

[0012] According to some preferred embodiments of the present invention, the amount of recycled aluminum added to the aluminum alloy material is greater than the amount of primary aluminum added. Preferably, the mass ratio between primary aluminum and recycled aluminum is 1:1.2-1.6. In the present invention, a larger proportion of recycled aluminum is used, and the formula design and preparation method are combined, so that the prepared aluminum alloy material still has good porosity and mechanical properties.

[0013] According to some preferred implementation aspects of the present invention, the porosity of the aluminum alloy material meets the D5 / 1 requirement, where D5 represents the area ratio of pore defects and 1 represents the diameter of the largest pore defect. Therefore, D5 / 1 means that the area ratio of pore defects is ≤5% and the diameter of the largest pore defect is ≤1 mm.

[0014] According to some preferred implementation aspects of the present invention, the aluminum alloy material has a yield strength of ≥120 MPa, a tensile strength of ≥250 MPa, and an elongation after fracture of ≥10%.

[0015] Preferably, the aluminum alloy material has a yield strength of 123-130 MPa, a tensile strength of 255-266 MPa, and an elongation after fracture of 10.5-12% at room temperature.

[0016] According to some preferred implementation aspects of the present invention, the density equivalent of the aluminum liquid before adding the aluminum strontium alloy during the preparation of the aluminum alloy material is ≤0.5%. The smaller the density equivalent, the lower the hydrogen content of the aluminum liquid, and the better the degassing and refining effect. Different products have different requirements for the density equivalent, and re-refining is required if the density equivalent is unqualified. According to the above formula and method in the present invention, the density equivalent of the obtained aluminum liquid is ≤0.5%.

[0017] According to some preferred implementation aspects of the present invention, the density equivalent is calculated according to the following formula: DI=(ρ-ρ1) / ρ; wherein: ρ is the density of the aluminum liquid at normal pressure; ρ1 is the density of the aluminum liquid at a vacuum pressure of -0.097 MPa, and the temperature of the aluminum liquid is 720°C±20°C.

[0018] According to some preferred implementation aspects of the present invention, the aluminum alloy material is suitable for high-pressure die casting of ≥4400T. In order to pursue mechanical properties, some heat-treatment-free materials in the prior art have poor fluidity of the materials, and are prone to cold shut and undercasting during die casting. The heat-treatment-free material in the present invention has high castability and can also be applied to thin-walled complex structural parts with high fluidity requirements, and can be applied to high-pressure die casting of ≥4400T.

[0019] The present invention also provides a method for preparing the high-strength and high-toughness die-cast aluminum alloy material without heat treatment as described above, comprising the following steps: The raw materials used to prepare the aluminum alloy material are melted, alloyed, and then refined; After refining, let it stand and conduct testing. After passing the test, add the deteriorating agent, mix well and then discharge; During the refining, the refining agent is first blown into the furnace with nitrogen and maintained for 20-30 minutes, and then nitrogen is introduced into the furnace for degassing for 15-20 minutes; the nitrogen is directly converted from liquid nitrogen on site and then blown into the furnace.

[0020] According to some preferred implementation aspects of the present invention, the detection includes a density equivalent test of the aluminum liquid, and the aluminum liquid is qualified when the density equivalent is ≤0.5%. By monitoring the density equivalent of the aluminum liquid, the quality of the aluminum liquid can be obtained more accurately, avoiding the subsequent low quality of the die casting.

[0021] According to some preferred implementation aspects of the present invention, the density equivalent test is: confirm that the temperature of the aluminum liquid is 720°C ± 20°C, first measure the density of the aluminum liquid under normal pressure, then evacuate the aluminum liquid, and measure the density of the aluminum liquid again under vacuum (-0.097Mpa pressure), and calculate the density equivalent based on the densities obtained from the two measurements.

[0022] According to some preferred implementation aspects of the present invention, the detection includes a slag content test; the K-mode value K≤2 / 20 is qualified, which means: 20 K-mode sections are taken for inspection, among which there are 2 or less impurity K-mode sections.

[0023] According to some preferred implementation aspects of the present invention, the modifier is an aluminum-strontium alloy, and the content of Sr element in the aluminum liquid during discharge is 0.016-0.026%.

[0024] According to some preferred embodiments of the present invention, the pressure of the nitrogen is 0.25-0.35 MPa.

[0025] The present invention also provides an application of the high-strength and high-toughness die-cast aluminum alloy material that does not require heat treatment as described above in the automotive field or the battery field.

[0026] The present invention also provides a thin-walled structural part prepared from the above-mentioned high-strength and high-toughness die-cast aluminum alloy material that does not require heat treatment. The thin-walled structural part has a size of 1200mm-1600mm and a thickness of 2-4mm.

[0027] According to some preferred embodiments of the present invention, the thin-walled structural member is a shock absorbing tower or a battery pack cross beam structural member.

[0028] Due to the adoption of the above technical scheme, compared with the prior art, the advantages of the present invention are: the high-strength and high-toughness die-cast aluminum alloy material that does not require heat treatment of the present invention reduces the needle-like Fe-rich phase through formula design and control of 5<Mn / Fe<7, thereby achieving the purpose of improving the mechanical properties of the aluminum alloy material, so that the aluminum alloy material has good porosity and good mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0030] Figure 1 This is a real photo of the shock absorbing tower prepared in Example 1 of the present invention; Figure 2 This is a porosity test diagram of the shock-absorbing tower prepared in Example 1 of the present invention; Figure 3 This is a porosity test diagram of the battery pack crossbeam prepared in Example 2 of the present invention; Figure 4 These are metallographic structure pictures of aluminum alloy materials, where (a) is the metallographic structure picture of the needle-shaped Fe-rich phase of the aluminum alloy material; (b) is the metallographic structure picture of the Chinese character-shaped Fe-rich phase of the aluminum alloy material. DETAILED DESCRIPTION

[0031] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0032] The heat-treatment-free high-strength and high-toughness die-cast aluminum alloy material of this embodiment includes, by mass percentage, silicon: 7-8%, iron: ≤0.14%, copper: ≤0.008%, manganese: 0.6-0.7%, magnesium: 0.2-0.26%, zinc: ≤0.005%, calcium: ≤0.001%, lead: ≤0.003%, antimony: ≤0.0003%, beryllium: ≤0.00008%, titanium: 0.08-0.15%, strontium: 0.016-0.026%; the remainder is impurities and aluminum, wherein the total impurities are ≤0.15%, a single impurity element is ≤0.05%, and the mass percentage content of manganese to the mass percentage content of iron is greater than 5 and less than 7 (5<Mn / Fe<7). Within a specific range, the use of Mn element to modify the cast aluminum alloy rich in Fe element can effectively transform the needle-shaped Fe-rich phase into the Chinese character-shaped Fe-rich phase, thereby achieving the effect of improving the strength of the alloy. However, excessive Mn content in the alloy will promote the formation of pores, so the ratio is controlled within 7. Figure 4 As shown, (a) is the metallographic structure picture of the needle-shaped Fe-rich phase of the aluminum alloy material; (b) is the metallographic structure picture of the Chinese character-shaped Fe-rich phase of the aluminum alloy material.

[0033] The raw materials used in the preparation of aluminum alloy materials include primary aluminum and recycled aluminum, electrolytic manganese, manganese additives (containing 75% manganese), pure magnesium ingots, aluminum-titanium alloy with a titanium content of 10%, 3303 specification metal silicon, and Al-Sr alloy with a Sr content of 10%. Primary aluminum is an A00 aluminum ingot with an aluminum content greater than 99.75%, and recycled aluminum is scrap aluminum with the same alloy grade as primary aluminum. The mass ratio between primary aluminum and recycled aluminum is 1:1.2-1.6, preferably 4:6, that is, the amount of recycled aluminum added is greater than the amount of primary aluminum added.

[0034] The yield strength of the aluminum alloy material is ≥120 MPa, the tensile strength is ≥250 MPa, and the elongation after fracture is ≥10%. Preferably, the yield strength of the aluminum alloy material at room temperature is 123-130 MPa, the tensile strength is 255-266 MPa, and the elongation after fracture is 10.5-12%. The test method for the mechanical properties (yield strength, tensile strength, elongation after fracture) of the aluminum alloy material refers to the method recorded in the national standard "GB / T 228-2002 Room Temperature Tensile Test Method for Metal Materials".

[0035] The preparation method of the heat-treatment-free high-strength and high-toughness die-cast aluminum alloy material of this embodiment has a process of smelting selection → melting (including slag removal) → alloying (including refinement) → refining (including component fine-tuning, modification, degassing and slag removal) → standing → inspection → soup extraction, and specifically includes the following steps: Step 1: Raw material selection The raw materials used include primary aluminum and recycled aluminum, electrolytic manganese, manganese additives (containing 75% manganese), pure magnesium ingots, aluminum-titanium alloy with a titanium content of 10%, 3303 specification metal silicon, and Al-Sr alloy with a Sr content of 10%. Primary aluminum is A00 aluminum ingots with an aluminum content greater than 99.75%, and recycled aluminum is scrap aluminum with the same alloy grade as primary aluminum. The mass ratio between primary aluminum and recycled aluminum is 4:6, that is, the amount of recycled aluminum added is greater than the amount of primary aluminum added.

[0036] Step 2: Melting A 10-20 ton reverberatory furnace is used, and the weight ratio of primary aluminum to recycled aluminum (aluminum scraps of the same alloy grade, such as hot molds, slag bags, material handles, etc.) is 4:6. The aluminum is melted three times. The first time, all the recycled aluminum is melted, the second time, half of the primary aluminum is melted, and the last time, the remaining half of the primary aluminum is melted. After stirring, remove the scum on the surface of the aluminum liquid to ensure that the cleanliness of the aluminum liquid is not affected by the recycled aluminum.

[0037] The volume of recycled aluminum is relatively smaller. It is first thrown into the bottom of the furnace to protect the furnace body and reduce the impact of large pieces of charge on the furnace wall. At the same time, the recycled aluminum has a lower melting point and is easy to melt. For the subsequent melting of primary aluminum with a higher melting point, it can improve the melting efficiency and reduce the burning loss. Then the primary aluminum is invaded into the aluminum liquid, which can also effectively reduce the oxidation of the recycled aluminum during the melting process due to contact with air and reduce hydrogen absorption and slag inclusion.

[0038] Step 3: Alloying According to the amount of molten aluminum liquid, add metal silicon that meets the composition requirements, the melting temperature is 760-780℃, the melting time is not less than 60 minutes, and the composition is confirmed by multi-point sampling in the furnace. According to the chemical composition of the aluminum liquid in the furnace, selectively add the raw materials of each component, and cool it down to control the temperature at 700℃-740℃ (the raw materials are added to achieve the cooling effect. If the temperature continues to be lowered, high-purity nitrogen needs to be blown into the furnace to cool it down. The combustion system can be used to increase the temperature). The composition is adjusted to: Silicon (Si): 7-8%, Iron (Fe): ≤0.14%, Copper (Cu) :≤0.008%; Manganese (Mn): 0.6-0.7%, Magnesium (Mg) 0.2-0.26%, Zinc (Zn) ≤0.005%, Calcium (Ca): ≤0.001%, Lead (Pb): ≤0.003%, Antimony (Sb): ≤0.0003%, Beryllium (Be): ≤0.00008%, Other individual impurity elements ≤0.05%, Total impurities ≤0.15%, The rest is aluminum (Al), and the mass percentage of manganese to iron is greater than 5 and less than 7 (5<Mn / Fe<7). After the composition is confirmed, add the refiner Al-Ti-B alloy to control the content of Ti element in the aluminum liquid to 0.08-0.15%.

[0039] Step 4: Refining Ensure that the aluminum liquid temperature is adjusted to between 700℃ and 740℃, add 0.2-0.4% of the aluminum liquid refining agent (YHRJ1-2 type refining agent) for refining and degassing, and proceed as follows: (1) Blow 0.2-0.4% of the refining flux powder and N2 into the furnace, where the pressure of N2 is 0.25-0.35MPa, and refine for 20-30 minutes; during the refining process, the refining flux powder and N2 are continuously blown in; (2) After step (1) is completed, N2 is introduced alone for degassing for 15 to 20 minutes. The degassing device is loaded by a forklift to evenly remove slag and gas in the furnace.

[0040] Step 5: Let stand After removing the aluminum slag on the surface of the aluminum liquid, let it stand for more than 10 minutes, and reconfirm the composition to ensure that the composition meets the requirements of silicon (Si): 7-8%, iron (Fe): ≤0.14%, copper (Cu): ≤0.008%; manganese (Mn): 0.6-0.7%, magnesium (Mg) 0.2-0.26%, zinc (Zn) ≤0.005%, Ca: ≤0.001%, Pb: ≤0.003%, Sb: ≤0.0003%, Be: ≤0.00008%, Ti: 0.08-0.15%, other single impurity elements ≤0.05%, the total impurities ≤0.15%, and the rest is aluminum (Al); and the ratio of the mass percentage of manganese to the mass percentage of iron is greater than 5 and less than 7 (5<Mn / Fe<7).

[0041] Step 6: Inspection After degassing, density equivalent test and slag content test are carried out. Density equivalent ≤ 0.5%, slag content K modulus K ≤ 2 / 20, both meet the conditions for qualified. If the test fails, re-refining is required.

[0042] The density equivalent in the present invention corresponds to the process of smelting. When the temperature of the aluminum liquid is confirmed to be 720℃±20℃, the density of the aluminum liquid is first measured at normal pressure, and then vacuum is drawn. The density of the aluminum liquid is measured again under vacuum, and the density equivalent is calculated based on the densities obtained from the two measurements. The density equivalent is calculated according to the following formula: DI=(ρ-ρ1) / ρ; where: ρ is the density of the aluminum liquid under normal pressure; ρ1 is the density of the aluminum liquid under vacuum (-0.097Mpa).

[0043] The smaller the density equivalent, the lower the hydrogen content of the aluminum liquid, and the better the degassing and refining effect. Different products have different requirements for density equivalent, and re-refining is required if the density equivalent is unqualified. According to the above method in this embodiment, the density equivalent of the obtained aluminum liquid is ≤0.5%. By monitoring the density equivalent of aluminum liquid, the quality of aluminum liquid can be obtained more accurately, avoiding the occurrence of low quality of die castings in the future.

[0044] K-mode value K≤2 / 20 means: 20 K-mode sections are checked, among which there are 2 or less impurity K-mode sections.

[0045] Step 7: Drain the soup Confirm that the aluminum liquid temperature is at 700℃±20℃, add the modifier aluminum strontium alloy, use N2 to stir rapidly, control the stirring time within 5min, control the Sr element content at 0.016-0.026%, and then prepare the soup.

[0046] Among them, the N2 used in steps 3), 4), and 7) is the liquid N2 converted into gaseous N2 at the smelting site and directly applied to the corresponding smelting process, which reduces the storage space. At the same time, the purity of N2 can reach 99.999%, which is higher and more stable, and has a good degassing effect. Combined with the refining and modification processes in the smelting of the present invention, the density equivalent can be ≤0.5%.

[0047] The high-strength and high-toughness die-cast aluminum alloy material obtained above that does not require heat treatment can be used for high-pressure die-casting to prepare thin-walled structural parts. The size of the thin-walled structural parts is 1200mm-1600mm and the thickness is 2-4mm; the thin-walled structural parts can be shock towers in the automotive field or battery pack crossbeam structural parts in the battery field. Example 1

[0048] The high-strength and high-toughness die-cast aluminum alloy material that does not require heat treatment in this embodiment has a chemical composition of: Si: 7.8%, Fe: 0.13%, Cu: 0.006%, Mn: 0.68%, Mg: 0.24%, Zn: 0.003%, Ti: 0.13%, Sr: 0.024%, Ca: 0.0008%, Pb: 0.0028%, Sb: 0.00028%, Be: 0.000077%, and the remainder is impurities and aluminum. The sum of other impurities is ≤0.15%, and the mass percentage content of manganese to the mass percentage content of iron Mn / Fe is 5.23.

[0049] The method for preparing the high-strength and high-toughness die-cast aluminum alloy material without heat treatment and the method for die-casting a large shock tower structure using the same in this embodiment include the following steps: 1) Raw material selection The raw materials include: primary aluminum, recycled aluminum, electrolytic manganese and manganese additives (containing 75% manganese), pure magnesium ingots, aluminum-titanium alloy with 10% titanium content; 3303 specification metal silicon, Al-Sr alloy with 10% Sr content. Primary aluminum is A00 aluminum ingot with an aluminum content greater than 99.75%, and recycled aluminum is scrap aluminum with the same alloy grade as primary aluminum. The mass ratio between primary aluminum and recycled aluminum is 4:6.

[0050] 2) Melting A 10-20 ton reverberatory furnace is used, and the weight ratio of primary aluminum and recycled aluminum (waste aluminum of the same alloy grade, such as hot molds, slag bags, material handles, etc.) is 4:6. The melting is carried out in three times. The first time all the recycled aluminum is melted, the second time half of the primary aluminum is melted, and the last time the remaining half of the primary aluminum is melted.

[0051] 3) Alloying According to the amount of molten aluminum liquid, add metal silicon that meets the preparation quantity requirements, the melting temperature is 760-780℃, the melting time is not less than 60 minutes, and the composition is confirmed by multi-point sampling in the furnace. According to the chemical composition of the aluminum liquid in the furnace, selectively add the raw materials of each component, and cool it down to control the temperature at 700℃-740℃ (the raw materials are added to achieve the cooling effect. If the temperature continues to be lowered, high-purity nitrogen needs to be blown into the furnace to cool it down. The combustion system can be used to increase the temperature). The composition is adjusted to: Silicon (Si): 7-8%, Iron (Fe): ≤0.14 %, copper (Cu): ≤0.008%; manganese (Mn): 0.6-0.7%, magnesium (Mg) 0.2-0.26%, zinc (Zn) ≤0.005%, Ca: ≤0.001%, Pb: ≤0.003%, Sb: ≤0.0003%, Be: ≤0.00008%, other single impurity elements ≤0.05%, total impurities ≤0.15%, the rest is aluminum (Al), and the mass percentage of manganese to iron is greater than 5 and less than 7 (5<Mn / Fe<7). After the composition is confirmed, add the refiner Al-Ti-B alloy and add the Ti element to 0.08-0.15%.

[0052] 4) Refining Ensure that the temperature of the aluminum liquid is adjusted to between 700℃ and 740℃, add refining agent for refining and degassing, and use (1) 0.2-0.4% refining agent powder and N2 to blow into the furnace together, with N2 pressure of 0.25-0.35MPa, and refine for 20-30 minutes; (2) introduce N2 alone and degas for 15-20 minutes. Use a forklift to load the degassing device to evenly remove slag and degas in the furnace.

[0053] 5) Let it stand After scraping off the aluminum slag on the surface of the aluminum liquid and letting it stand for more than 10 minutes, reconfirm the composition to ensure that the composition meets the requirements of silicon (Si): 7-8%, iron (Fe): ≤0.14%, copper (Cu): ≤0.008%; manganese (Mn): 0.6-0.7%, magnesium (Mg) 0.2-0.26%, zinc (Zn) ≤0.005%, Ca: ≤0.001%, Pb: ≤0.003%, Sb: ≤0.0003%, Be: ≤0.00008%, Ti: 0.08-0.15%, other single impurity elements ≤0.05%, the total impurities ≤0.15%, and the rest is aluminum (Al); and the ratio of the mass percentage of manganese to the mass percentage of iron is greater than 5 and less than 7 (5<Mn / Fe<7).

[0054] 6) Inspection After degassing, density equivalent test and slag content test are carried out. Density equivalent ≤ 0.5%, slag content K modulus K ≤ 2 / 20, both meet the conditions for qualified. If the test fails, re-refining is required.

[0055] 7) Drain the soup Confirm that the aluminum liquid temperature is at 700℃±20℃, add the modifier aluminum strontium alloy, use N2 to stir quickly (control within 5 minutes), control the Sr element content to 0.016-0.026%, and then make soup.

[0056] It should be pointed out here that the N2 used in steps 3), 4), and 7) is converted from liquid N2 to gaseous N2 at the smelting site and immediately applied to the corresponding smelting process. The purity of the N2 obtained by this method can reach 99.999%, and the degassing effect is good. In combination with the refining and modification processes in the smelting of the present invention, the density equivalent can be ≤0.5%. The smaller the density equivalent, the lower the hydrogen content of the aluminum liquid, and the better the degassing and refining effect.

[0057] 8) Die casting process The aluminum alloy liquid temperature was controlled at 660-680℃, the die-casting machine clamping force was 4500kN, and the die-casting machine cake thickness was 45mm; the mold temperature controller was used to control the mold surface temperature, the set temperature was 200℃, the casting pressure was 70 MPa, the injection time was 12s, and the cooling time was 25s. Among them, the punch stroke position during die casting was: when the punch stroke reached 100mm, the speed was 0.2m / s, when the punch stroke reached 550mm, the speed was 4.5m / s, and when the punch stroke reached 670mm, the pressure was increased, the pressure value was 60%, and the time was 2s. A high-toughness aluminum alloy cast shock-absorbing tower was prepared.

[0058] The high-toughness aluminum alloy cast shock-absorbing tower prepared in this embodiment is as follows: Figure 1As shown, its room temperature tensile strength is 255-261 MPa, yield strength is 123-128 MPa, and elongation after break is 10.5-11.2%. The product is assembled by the main engine factory and then road tested, and all indicators meet the use requirements.

[0059] The porosity of the high-toughness aluminum alloy cast shock-absorbing tower prepared in this embodiment was tested. Figure 2 shown. Figure 2 In the selected area, the porosity is 0.12% and the diameter of the largest pore defect is 0.54 mm, which meets the porosity requirement of D5 / 1. Example 2

[0060] The high-strength and high-toughness die-cast aluminum alloy material that does not require heat treatment in this embodiment has a chemical composition of: Si: 7.3%, Fe: 0.10%, Cu: 0.007%, Mn: 0.65%, Mg: 0.25%, Zn: 0.003%, Ti: 0.13%, Sr: 0.024%, Ca: 0.0008%, Pb: 0.0028%, Sb: 0.00028%, Be: 0.000077%, and the remainder is impurities and aluminum. The sum of other impurities is ≤0.15%, and the ratio of the mass percentage content of manganese to the mass percentage content of iron Mn / Fe is 6.5.

[0061] The preparation method of the high-strength and high-toughness die-cast aluminum alloy material without heat treatment in this embodiment is basically the same as that in Example 1, and will not be repeated here. The steps of die-casting the battery pack cross beam structural member using the high-strength and high-toughness die-cast aluminum alloy material without heat treatment are as follows: The aluminum alloy liquid temperature was controlled at 660-680℃, the die-casting machine clamping force was 4200kN, and the die-casting machine cake thickness was 40mm; the mold temperature controller was used to control the mold surface temperature, the set temperature was 200℃, the casting pressure was 75 MPa, the injection time was 10s, and the cooling time was 22s. The punch stroke position during die casting was: when the punch stroke reached 100mm, the speed was 0.2m / s, when the punch stroke reached 530mm, the speed was 4.0m / s, and when the punch stroke reached 640mm, the pressure was increased, the pressure value was 70%, and the time was 2s. The battery pack crossbeam structural parts were prepared.

[0062] The prepared high-toughness aluminum alloy cast battery pack crossbeam has a room temperature tensile strength of 258-266 MPa, a yield strength of 124-130 MPa, and an elongation at break of 10.8-11.9%.

[0063] The porosity of the high-toughness aluminum alloy cast battery pack crossbeam prepared in this embodiment was tested. Figure 3 shown. Figure 3In the selected area, the porosity is 0.04% and the diameter of the largest pore defect is 0.41 mm, which meets the porosity requirement of D5 / 1. Comparative Example 1

[0064] The aluminum alloy material of this comparative example has a chemical composition of Si: 7.6%, Fe: 0.13%, Cu: 0.007%, Mn: 0.68%, Mg: 0.28%, Zn: 0.003%, Ti: 0.13%, Sr: 0.010%, Ca: 0.0008%, Pb: 0.0028%, Sb: 0.00026%, Be: 0.00008%, and the remainder is impurities and aluminum. The sum of other impurities is ≤0.2%, and the ratio of the mass percentage content of manganese to the mass percentage content of iron (Mn / Fe) is 5.23.

[0065] The aluminum alloy cast shock-absorbing tower is prepared by the die-casting method in Example 1 using the above aluminum alloy material, and has a room temperature tensile strength of 223-234 MPa, a yield strength of 122-125 MPa, and an elongation after fracture of 9.3-9.9%.

[0066] The main difference between the aluminum alloy material of this comparative example and Example 1 is that the Sr content is relatively low, resulting in an increase in primary silicon, a significant decrease in mechanical properties, a decrease in maximum tensile strength from 261 MPa to 234 MPa, a decrease in maximum yield strength from 128 MPa to 125 MPa, and a decrease in maximum elongation after fracture from 11.2% to 9.9%. The remaining steps and parameters are basically the same as those of Example 1. Comparative Example 2

[0067] The aluminum alloy material of this comparative example has a chemical composition of: Si: 7.3%, Fe: 0.14%, Cu: 0.007%, Mn: 0.65%, Mg: 0.25%, Zn: 0.003%, Ti: 0.13%, Sr: 0.024%, Ca: 0.0008%, Pb: 0.0028%, Sb: 0.00028%, Be: 0.000077%, and the remainder is impurities and aluminum. The sum of other impurities is ≤0.15%, and the ratio of the mass percentage content of manganese to the mass percentage content of iron (Mn / Fe) is 4.64.

[0068] The above-mentioned aluminum alloy material is used to prepare an aluminum alloy cast battery pack crossbeam based on the die-casting method in Example 2, with a room temperature tensile strength of 230-247 MPa, a yield strength of 118-128 MPa, and an elongation after fracture of 8.1-9.4%.

[0069] The main difference between the aluminum alloy material of this comparative example and Example 2 is that: Mn / Fe is relatively low, the Mn content is relatively small, and it can only replace part of the Fe element to form a-A1(Mn,Fe)Si, and most of it is still a needle-shaped Fe-rich phase, so the mechanical properties are reduced, the maximum tensile strength is reduced from 266MPa to 247MPa, the maximum yield strength is reduced from 130MPa to 128MPa, and the maximum elongation after fracture is reduced from 11.9% to 9.4%. The remaining steps and parameters are basically the same as those of Example 2.

[0070] Comparative Example 3 (Mn / Fe greater than 7) The aluminum alloy material of this comparative example has a chemical composition of: Si: 7.3%, Fe: 0.10%, Cu: 0.007%, Mn: 0.75%, Mg: 0.25%, Zn: 0.003%, Ti: 0.13%, Sr: 0.022%, Ca: 0.0008%, Pb: 0.0028%, Sb: 0.00028%, Be: 0.000077%, and the remainder is impurities and aluminum. The sum of other impurities is ≤0.15%, and the ratio of the mass percentage content of manganese to the mass percentage content of iron (Mn / Fe) is 7.5.

[0071] The above-mentioned aluminum alloy material is used to prepare an aluminum alloy cast battery pack crossbeam based on the die-casting method in Example 2, with a room temperature tensile strength of 223-237 MPa, a yield strength of 114-127 MPa, and an elongation after fracture of 8.9-9.6%.

[0072] The main difference between the aluminum alloy material of this comparative example and Example 2 is that the Mn / Fe ratio is increased from 6.5 to 7.5, and under the same other conditions, the maximum tensile strength is reduced from 266MPa to 237MPa, the maximum yield strength is reduced from 130MPa to 127MPa, and the maximum elongation after fracture is reduced from 11.9% to 9.6%. The remaining steps and parameters are basically the same as those of Example 2. Comparative Example 4

[0073] The aluminum alloy material of this comparative example has a chemical composition of: Si: 9.3%, Fe: 0.14%, Cu: 0.007%, Mn: 0.65%, Mg: 0.25%, Zn: 0.003%, Ti: 0.13%, Sr: 0.022%, Ca: 0.0008%, Pb: 0.0028%, Sb: 0.00028%, Be: 0.000077%, and the remainder is impurities and aluminum. The sum of other impurities is ≤0.15%, and the ratio of the mass percentage content of manganese to the mass percentage content of iron (Mn / Fe) is 4.64.

[0074] The above-mentioned aluminum alloy material is used to prepare an aluminum alloy cast battery pack crossbeam based on the die-casting method in Example 2, with a room temperature tensile strength of 234-245 MPa, a yield strength of 112-125 MPa, and an elongation after fracture of 9.1-9.5%.

[0075] The main difference between the aluminum alloy material of this comparative example and Example 2 is that the Si content is relatively high and the Mn / Fe is relatively low; referring to Comparative Example 2, under the condition that Mn / Fe is 4.64, the Si content is greater than 8%, the maximum tensile strength is reduced from 266MPa to 245MPa, the maximum yield strength is reduced from 130MPa to 125MPa, and the maximum elongation after fracture is reduced from 11.9% to 9.5%. The remaining steps and parameters are basically the same as those of Example 2.

[0076] Comparative Example 5 (Density equivalent of aluminum liquid> 0.5%) The aluminum alloy material of this comparative example has a chemical composition of Si: 7.8%, Fe: 0.13%, Cu: 0.006%, Mn: 0.68%, Mg: 0.24%, Zn: 0.003%, Ti: 0.13%, Sr: 0.024%, Ca: 0.0008%, Pb: 0.0028%, Sb: 0.00028%, Be: 0.000077%, and the remainder is impurities and aluminum. The sum of other impurities is ≤0.15%, and the ratio of the mass percentage content of manganese to the mass percentage content of iron (Mn / Fe) is 5.23.

[0077] The aluminum alloy cast shock-absorbing tower is prepared by the die-casting method in Example 1 using the above aluminum alloy material, and has a room temperature tensile strength of 228-234 MPa, a yield strength of 109-115 MPa, and an elongation after fracture of 7.2-9%.

[0078] The main difference between the aluminum alloy material in this comparative example and that in Example 1 is that commercially available gaseous nitrogen is directly used for refining and purging during refining, so that the density equivalent of the aluminum liquid is 0.6%, the cleanliness of the aluminum liquid is poor, and the K modulus value K≤2 / 20, which leads to a decrease in the mechanical properties of the final material, the maximum tensile strength is reduced from 261 MPa to 234 MPa, the maximum yield strength is reduced from 128 MPa to 115 MPa, and the maximum elongation after fracture is reduced from 11.2% to 9%.

[0079] Some heat-treatment-free materials in the prior art have poor flow properties in order to pursue mechanical properties, and are prone to cold shut and undercasting during die casting. The heat-treatment-free materials in the present invention have high castability and are also suitable for thin-walled complex structural parts with high fluidity requirements, and can be suitable for high-pressure die casting of ≥4400T. The purpose of the present invention is to: 1) develop a high-strength and high-toughness aluminum alloy that does not require heat treatment, which is used for complex thin-walled automotive structural parts, wherein the yield strength is ≥120 MPa and the tensile strength is ≥250 MPa, elongation after fracture ≥ 10%; 2) At present, the raw materials used for domestic heat treatment-free aluminum alloys are mostly primary aluminum, and the energy consumption for producing primary aluminum is 20 times that of recycled aluminum. The present invention uses recycled aluminum with a larger proportion, such as hot molds, slag bags, material handles and other scrap aluminum, which do not need to be remelted and are directly returned to the furnace, saving a large amount of remelting aluminum ingot costs. The disadvantage is that compared with remelting aluminum ingots, scrap aluminum has high impurities and is difficult to smelt, and the mechanical properties of the alloy may not be as good as the corresponding alloy of remelting aluminum ingots with fewer impurities; therefore, the preparation method of the present invention can obtain a high density aluminum alloy with a higher proportion of recycled aluminum and without the need for additional filtration. Aluminum liquid with an equivalent of ≤0.5% and high-strength and high-toughness aluminum alloy materials that do not require heat treatment, the subsequent die-castings can maintain good yield strength, tensile strength, and elongation after fracture; 3) Provide a low-cost high-strength and high-toughness aluminum alloy that does not require heat treatment. At present, rare earth and other high-cost trace elements are generally added to the raw materials to meet the use requirements of the automotive industry. The alloy elements selected for the aluminum raw materials of the present invention are relatively low in cost. Only through the matching mechanism between the element types, the content ratio and the high-quality control of smelting (density equivalent ≤0.5%), complex large-scale thin-walled structural parts that meet the requirements of the automotive industry can be produced.

[0080] Beneficial effects of the present invention: 1. The present invention can be applied to the die-casting production of complex large-scale thin-walled structural parts, which is not easy to stick to the mold, has low porosity (satisfying D5 / 1, that is, the area of ​​pore defects ≤5%, and the maximum pore defect diameter ≤1mm), and strong resistance to thermal cracking. 2. The high-strength and high-toughness aluminum alloy of the present invention has a yield strength ≥120 MPa, a tensile strength ≥250 MPa, and an elongation after fracture ≥10%, which meets the automotive industry's use requirements for complex large-scale thin-walled structural parts. 3. The alloy elements selected by the present invention do not contain high-cost elements such as rare earths, have high cost performance, and are suitable for a wide range of applications.

[0081] The above embodiments prepared by the method of the present invention are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit and essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-strength and high-toughness die-cast aluminum alloy material that does not require heat treatment, characterized in that: Measured by mass percentage, the aluminum alloy material includes silicon: 7-8%, iron: ≤0.14%, copper: ≤0.008%, manganese: 0.6-0.7%, magnesium: 0.2-0.26%, zinc: ≤0.005%, calcium: ≤0.001%, lead: ≤0.003%, antimony: ≤0.0003%, beryllium: ≤0.00008%, titanium: 0.08-0.15%, strontium: 0.016-0.026%; the remainder is impurities and aluminum, wherein the total impurities are ≤0.15%, a single impurity element is ≤0.05%, and the ratio of the mass percentage content of manganese to the mass percentage content of iron is greater than 5 and less than 7.

2. The aluminum alloy material according to claim 1, characterized in that: The raw materials of the aluminum alloy material include primary aluminum and recycled aluminum, electrolytic manganese and manganese additives, magnesium ingots, aluminum-titanium alloy, metal silicon and aluminum-strontium alloy.

3. The aluminum alloy material according to claim 2, characterized in that: The primary aluminum is an A00 aluminum ingot with an aluminum content greater than 99.75%, and the recycled aluminum is scrap aluminum with the same alloy grade as the primary aluminum.

4. The aluminum alloy material according to claim 3, characterized in that: The amount of recycled aluminum added to the aluminum alloy material is greater than the amount of primary aluminum added.

5. The aluminum alloy material according to claim 1, characterized in that: The area of ​​pore defects in the aluminum alloy material accounts for ≤5%, and the maximum pore defect diameter is ≤1mm.

6. The aluminum alloy material according to claim 1, characterized in that: The aluminum alloy material has a yield strength of ≥120 MPa, a tensile strength of ≥250 MPa, and an elongation after fracture of ≥10%.

7. The aluminum alloy material according to claim 6, characterized in that: The aluminum alloy material has a yield strength of 123-130 MPa, a tensile strength of 255-266 MPa, and an elongation after fracture of 10.5-12% at room temperature.

8. The aluminum alloy material according to any one of claims 1 to 7, characterized in that: During the preparation of the aluminum alloy material, the density equivalent of the aluminum liquid before adding the aluminum strontium alloy is ≤0.5%.

9. The aluminum alloy material according to claim 8, characterized in that: The density equivalent is calculated according to the following formula: DI=(ρ-ρ1) / ρ; wherein: ρ is the density of the aluminum liquid under normal pressure; ρ1 is the density of the aluminum liquid under vacuum, and the temperature of the aluminum liquid is 720°C±20°C.

10. The aluminum alloy material according to claim 1, characterized in that: The aluminum alloy material is suitable for high-pressure die casting with a pressure of ≥4400T.

11. A method for preparing a high-strength and high-toughness die-cast aluminum alloy material without heat treatment as claimed in any one of claims 1 to 10, characterized in that: The steps include: The raw materials used to prepare the aluminum alloy material are melted, alloyed, and then refined; After refining, let it stand and conduct testing. After passing the test, add the deteriorating agent, mix well and then discharge; During the refining, the refining agent is first blown into the furnace with nitrogen and maintained for 20-30 minutes, and then nitrogen is introduced into the furnace for degassing for 15-20 minutes; the nitrogen is directly converted from liquid nitrogen on site and then blown into the furnace.

12. The preparation method according to claim 11, characterized in that: The test includes a density equivalent test of the aluminum liquid, and the aluminum liquid is qualified if the density equivalent is ≤0.5%.

13. The preparation method according to claim 12, characterized in that: The density equivalent test is as follows: confirm that the aluminum liquid temperature is 720°C ± 20°C, first measure the density of the aluminum liquid under normal pressure, then evacuate the aluminum liquid, and measure the density of the aluminum liquid again under vacuum, and calculate the density equivalent based on the densities obtained from the two measurements.

14. The preparation method according to claim 11, characterized in that: The test includes a slag content test; a K modulus value K≤2 / 20 is qualified.

15. The preparation method according to claim 11, characterized in that: The modifier is an aluminum-strontium alloy, and the content of strontium in the aluminum liquid during discharge is 0.016-0.026%.

16. The preparation method according to claim 11, characterized in that: The pressure of the nitrogen is 0.25-0.35 MPa.

17. Use of the high-strength and high-toughness die-cast aluminum alloy material that does not require heat treatment as claimed in any one of claims 1 to 10 in the automotive field or the battery field.

18. A thin-walled structural part made from the high-strength and high-toughness die-cast aluminum alloy material that does not require heat treatment as described in any one of claims 1 to 10.

19. The thin-walled structural member according to claim 18, characterized in that: The thin-walled structural member has a size of 1200 mm to 1600 mm and a thickness of 2 to 4 mm.

20. The thin-walled structural member according to claim 18, characterized in that: The thin-walled structural member is a shock-absorbing tower or a battery pack crossbeam structural member.

Citation Information

Patent Citations

  • A heat-treasure-free high-strength and high-toughness die-cast aluminum alloy, its preparation method and products

    CN115961183B

  • High-yield heat-treatment-free aluminum alloy material for thin-wall welding process of new energy automobile and preparation method thereof

    CN117265344A

  • A renewable high-strength and tough heat-treatment-free aluminum alloy and its preparation method and die-casting process

    CN117448634B

  • Aluminum-silicon alloy doped with iron element and copper element

    CN103088240A

  • Al-Si heat-treatment-free aluminum alloy as well as preparation method and application thereof

    CN116987936A

Cited By

  • Aluminum alloy material for vehicle body and preparation method therefor

    WO2026184387A1